A symmetric cryptosystem based on nondeterministic finite automata - Khaleel, Ghassan; Turaev, Sherzod; Alshaikhli, Imad Fakhri Taha; Zhukabayeva, Tamara; Mohd Tamrin, Mohd Izzuddin (Asian Research Publishing Network (ARPN), 2017)
This paper proposes a new symmetric cryptosystem based on nondeterministic finite automata. It is shown that nondeterminism allows to reduce the dependency of key automata on a large descriptional complexity and irreversibility of the automata. Moreover, it is proven that the introduced cryptosystem has higher security and more efficient performance than its deterministic counterparts, Domosi’s cryptosystem and the modified Domosi’s cryptosystem.